Career preference of secondary school students in relation to their parental involvement - Krishan Gopal Kansal; Asha Yadav (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present paper was taken up with broad objective to study the career preference of secondary school students in relation to their parental involvement. For this study, a sample of 560 secondary school students was drawn randomly from the Malwa region of Punjab. Different schools from the Malwa region were chosen using a multi-stage cluster sampling technique. The Career Preference Inventory developed by the investigator was used to collect the data. To analyse the data, percentage statistics and a t-test were used. The results show that the top three career preferences of secondary school students are Defence Forces (20.00%), Teaching & Training (19.82%), and Law Enforcement & Administrative (11.25%). The study found that there is a significant difference in career preferences of secondary school students in Law Enforcement & Administrative with respect to their parental involvement. It is suggested that every parent should encourage and motivate their child for choosing suitable courses.